Heat-conducting phase change coating and preparation method thereof
By selecting suitable adhesives, initiators, thermal fillers and phase change materials among the phase change materials, and adding wetting and dispersing agents, a phase change coating with high thermal conductivity and stability is prepared, which solves the problems of weakening the pooling strength and slow thermal conductivity at high temperatures of existing phase change materials, and achieves efficient heat conduction and long-term stability.
Patent Information
- Application Number
- CN202510004929.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing phase change materials weaken their strength at continuous high temperatures, resulting in increased thermal resistance of component separation and slow thermal conductivity, making it impossible to dissipate heat in time.
By selecting a binder composed of multiple combination materials, using benzoyl peroxide as the initiator, selecting expanded graphite with rich pore structure as the thermal filler, using paraffin as the phase change material, and adding wetting dispersant, a phase change coating with high thermal conductivity, high heat absorption and material stability is prepared.
It realizes maintaining high thermal conductivity under high temperature environments, avoiding increased thermal resistance, and improving thermal conductivity and device service life.
Smart Images

Figure CN119799104A_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the field of phase change materials, and in particular relates to a thermal conductive phase change coating and a preparation method thereof. Background technology:
[0002] Thermally conductive phase change materials are materials that change their physical state as temperature changes. They are mainly used to reduce the thermal resistance between electronic devices and heat sinks, thereby improving heat dissipation efficiency. These materials are solid at room temperature, making them easy to handle and install. When the temperature of the electronic device rises during operation, the phase change material absorbs heat and changes from solid to liquid or soft, thereby filling the tiny gap between the device and the heat sink, effectively removing air from the interface, and greatly reducing the thermal resistance between the contact surfaces. The phase change process of this material is accompanied by the absorption or release of latent heat, which gives it significant advantages in the field of electronic heat dissipation.
[0003] Due to the excellent thermal conductivity of phase change materials, they are widely used in computer / notebook high-computing module devices, high-frequency microprocessors, memory modules, DC / DC converters and power modules and other electronic devices for efficient heat dissipation of various devices. However, when the device continues to operate at a high temperature, the cohesiveness of the phase change material may be weakened by the temperature, resulting in separation between the components, thereby increasing thermal resistance. In addition, existing phase change materials often have problems such as slow thermal conductivity, inability to dissipate heat in time, and small enthalpy of absorbed heat.
[0004] Chinese patent CN112048221A discloses a method for preparing a phase-change energy-saving material, which realizes the temperature-changing regulation effect by preparing a phase-change material with expanded graphite and mixed acid. Chinese patent CN108531024A discloses a method for preparing a high thermal conductivity coating, which improves the high thermal conductivity of the material by preparing a modified boron nitride nanosheet / nano-titanium oxide composite material.
[0005] Different from this, the present invention obtains a phase change coating with high thermal conductivity, high heat absorption and good material stability through research on temperature change materials, adhesives, thermal conductive fillers, etc. The thermal conductive phase change material of the present invention can be widely used in many fields such as electronics, aerospace, etc., and can be used in complex environmental factors such as continuous high temperature changes and high-frequency vibrations to maintain good thermal conductivity and heat dissipation performance. Summary of the invention:
[0006] In view of the above shortcomings of the prior art, the present invention provides a thermally conductive phase change coating and a preparation method thereof.
[0007] The first object of the present invention is to provide a thermally conductive phase change coating.
[0008] The components of a thermally conductive phase-change coating of the present invention include an adhesive material, a solvent, an initiator, a thermally conductive filler, a phase-change material and a wetting dispersant.
[0009] The adhesive composition is a mixture of isooctyl acrylate, vinyl acetate and acrylic acid. Further, it includes 12% to 14% isooctyl acrylate, 4% to 6% vinyl acetate and 2% to 4% acrylic acid. In some embodiments, isooctyl acrylate: vinyl acetate: acrylic acid 8.7:3.3:2. The inventors have found through research that selecting a multi-combination material to form an adhesive is beneficial to improving the cohesive strength of the coating structure, that is, when the operating temperature is continuously high, the phase change material still maintains a good cohesive strength, the components do not separate, the phase change coating does not dry out and harden, and the thermal resistance does not increase.
[0010] The initiator is benzoyl peroxide, accounting for 0.1% to 0.5%. Further, the ratio of the initiator to the adhesive is 0.2:14 to 0.2:21. In some embodiments, the initiator prescription ratio is 0.2%.
[0011] The solvent is an organic solvent. Specifically, the organic solvent of the present invention is toluene, which accounts for 8% to 10%.
[0012] The thermal conductive filler is preferably an inert material with a rich pore structure. Specifically, the thermal conductive material of the present invention is expanded graphite, which accounts for 2% to 5%. Further, the expanded graphite has a density of 1.5 to 2.1 g / cm 3 , the crystal particle size is 0.15~0.3mm, and the expanded graphite with this density and particle size range can play a good role in thermal conductivity. Obviously, the expanded graphite with rich pore structure can effectively improve the energy storage and release efficiency, and solve the problem of poor thermal conductivity of traditional phase change thermal storage materials.
[0013] The phase change material of the present invention is a mixture of short-chain hydrocarbons extracted from petroleum. Specifically, the phase change material selected by the present invention is paraffin, white vaseline, etc. This type of mixture has a large melting range and can effectively absorb environmental heat. In some embodiments, paraffin is preferably selected, accounting for 50% to 70%, and more preferably 60% to 70%. Further, the phase change paraffin is a straight-chain alkane with 26 carbon atoms. The present invention finds that the phase change material at this ratio can effectively increase the phase change enthalpy value of the coating.
[0014] The wetting and dispersing agent can be selected from polyamino cationic perylene imide graphene dispersants, accounting for 1% to 5%; further accounting for 2% to 4%. In some embodiments, the wetting and dispersing agent accounts for 2%. The ratio of the wetting and dispersing agent to the expanded graphite ranges from 2:3 to 2:8. Within this ratio range, the dispersion of the expanded graphite can be well promoted, so that the small particle size and light density expanded graphite can be evenly dispersed in the coating, avoiding agglomeration, thereby improving the thermal conductivity efficiency of the material.
[0015] Specifically, a better solution of the present invention may be as follows:
[0016] The weight percentage content of each component of the raw material is:
[0017] Isooctyl acrylate: 12%~14%
[0018] Vinyl acetate: 4% to 6%
[0019] Acrylic acid: 2% to 4%
[0020] Toluene: 8%~10%
[0021] Benzoyl peroxide: 0.2%
[0022] Expanded graphite: 2%~5%
[0023] Phase change paraffin: 60%~70%
[0024] Wetting and dispersing agent: 2%.
[0025] The second object of the present invention is to provide a method for preparing a thermally conductive phase change coating.
[0026] The preparation process steps are:
[0027] (1) Add 2-ethylhexyl acrylate, 2-ethylhexyl acetate, acrylic acid, and part of toluene into a 4-necked reaction bottle, and set the external temperature to above 82°C.
[0028] (2) When the temperature of the material in the bottle rises to 79°C, the BPO solution dissolved in the remaining toluene is evenly added dropwise into the reaction bottle within 2 hours.
[0029] (3) Keep the reaction warm for 2 hours.
[0030] (4) Add phase change paraffin and wetting dispersant into the reaction bottle and stir rapidly for 30 minutes.
[0031] (5) Slowly add expanded graphite into the reaction bottle in batches.
[0032] (6) After stirring and dispersing for 120 minutes, the mixture is applied while maintaining the temperature.
[0033] The present invention is a phase change coating with high thermal conductivity, high heat absorption and good material stability. It can be used alone or in combination in many fields such as electronics, aerospace, etc. It has good thermal conductivity, non-conductivity, good reliability and long-term stability, and can maintain stable performance under harsh temperature conditions.
[0034] Beneficial effects of the present invention:
[0035] 1. The phase change coating of the present invention has a high enthalpy value of thermal conductive phase change. Specifically, the enthalpy values of the samples of the embodiments of the present invention are all above 130 j / g, indicating that the present invention absorbs more heat during the thermal change process, which is more conducive to dissipating more heat and reducing the accumulation of heat between devices.
[0036] 2. The thermal conductive filler of the present invention is selected from expanded graphite with rich pore structure and a density of 1.5-2.1 g / cm 3 The crystal particle size is between 0.15 and 0.3 mm, which can effectively improve the energy storage and release efficiency, improve thermal conductivity, dissipate heat in time, and increase the service life of the device.
[0037] 3. The coating of the present invention has high cohesive strength. The peeling force does not change after being placed at 85°C (85% humidity), indicating that the adhesion strength between the coating and the release film has not changed, and further indicating that the cohesive strength of the coating has not changed. That is, when the operating temperature is continuously high, the phase change material still maintains a good cohesive strength, the components do not separate, the phase change coating does not dry out and harden, and the thermal resistance does not increase.
[0038] 4. The present invention is easy to prepare and use. The material can be coated as a whole at high temperature and then packaged with different materials. It can be used in a solid state, which is convenient for installation and handling. Description of the drawings:
[0039] Figure 1 is the DSC diagram of Example 1;
[0040] Figure 2 is the DSC diagram of Example 2;
[0041] Figure 3 This is the DSC chart of Example 3. Specific implementation method:
[0042] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0043] Example 1
[0044] Weigh the ingredients as follows:
[0045] Isooctyl acrylate: 13g
[0046] Vinyl acetate: 5g
[0047] Acrylic acid: 3g
[0048] Toluene: 9g
[0049] Benzoyl peroxide: 0.2g
[0050] Expanded graphite: 7.8g
[0051] Phase change paraffin: 60g
[0052] Polyamino cationic perylene imide graphene dispersant: 2g
[0053] A. The expanded graphite has a density of 1.5-2.1g / cm 3 , the crystal particle size is 0.15-0.3mm.
[0054] B. The phase change paraffin is a straight chain alkane with 26 carbon atoms.
[0055] C. The purity of isooctyl acrylate, vinyl acetate, acrylic acid, toluene and benzoyl peroxide is greater than 99.9%.
[0056] Preparation method of the above phase change coating:
[0057] ①Put isooctyl acrylate, isooctyl acetate, acrylic acid and part of toluene into a 4-necked reaction bottle and set the external temperature to 82°C.
[0058] ② When the temperature of the material in the bottle rises to 79°C, add the BPO solution dissolved in the remaining toluene evenly into the reaction bottle within 2 hours.
[0059] ③ Keep the reaction warm for 2 hours.
[0060] ④Put the phase change paraffin and wetting dispersant into the reaction bottle and stir rapidly for 30 minutes.
[0061] ⑤ Slowly add expanded graphite into the reaction bottle in batches.
[0062] ⑥ After stirring and dispersing for 120 minutes, apply the mixture while maintaining the temperature.
[0063] Example 2
[0064] Weigh the ingredients as follows:
[0065] Isooctyl acrylate: 10g
[0066] Vinyl acetate: 5g
[0067] Acrylic acid: 3g
[0068] Toluene: 9g
[0069] Benzoyl peroxide: 0.2g
[0070] Expanded graphite: 3.8g
[0071] Phase change paraffin: 67g
[0072] Polyamino cationic perylene imide graphene dispersant: 2g
[0073] A. The expanded graphite has a density of 1.5-2.1g / cm 3 , the crystal particle size is 0.15-0.3mm.
[0074] B. The phase change paraffin is a straight chain alkane with 26 carbon atoms.
[0075] C. The purity of isooctyl acrylate, vinyl acetate, acrylic acid, toluene and benzoyl peroxide is greater than 99.9%.
[0076] Preparation method of the above phase change coating:
[0077] ①Put isooctyl acrylate, isooctyl acetate, acrylic acid and part of toluene into a 4-necked reaction bottle and set the external temperature to 82°C.
[0078] ② When the temperature of the material in the bottle rises to 79°C, add the BPO solution dissolved in the remaining toluene evenly into the reaction bottle within 2 hours.
[0079] ③ Keep the reaction warm for 2 hours.
[0080] ④Put the phase change paraffin and wetting dispersant into the reaction bottle and stir rapidly for 30 minutes.
[0081] ⑤ Slowly add expanded graphite into the reaction bottle in batches.
[0082] ⑥ After stirring and dispersing for 120 minutes, apply the mixture while maintaining the temperature.
[0083] Example 3
[0084] Weigh the ingredients as follows:
[0085] Isooctyl acrylate: 8.7g
[0086] Vinyl acetate: 3.3g
[0087] Acrylic acid: 2g
[0088] Toluene: 6g
[0089] Benzoyl peroxide: 0.2g
[0090] Expanded graphite: 7.8g
[0091] Phase change paraffin: 70g
[0092] Polyamino cationic perylene imide graphene dispersant: 2g
[0093] A. The expanded graphite has a density of 1.5-2.1g / cm 3 , the crystal particle size is 0.15-0.3mm.
[0094] B. The phase change paraffin is a straight chain alkane with 26 carbon atoms.
[0095] C. The purity of isooctyl acrylate, vinyl acetate, acrylic acid, toluene and benzoyl peroxide is greater than 99.9%.
[0096] Preparation method of the above phase change coating:
[0097] ①Put isooctyl acrylate, isooctyl acetate, acrylic acid and part of toluene into a 4-necked reaction bottle and set the external temperature to 82°C.
[0098] ② When the temperature of the material in the bottle rises to 79°C, add the BPO solution dissolved in the remaining toluene evenly into the reaction bottle within 2 hours.
[0099] ③ Keep the reaction warm for 2 hours.
[0100] ④Put the phase change paraffin and wetting dispersant into the reaction bottle and stir rapidly for 30 minutes.
[0101] ⑤ Slowly add expanded graphite into the reaction bottle in batches.
[0102] ⑥ After stirring and dispersing for 120 minutes, apply the mixture while maintaining the temperature.
[0103] Experimental Results
[0104] (1) Thermal phase change performance test
[0105] Equipment: Differential Scanning Calorimeter
[0106] Manufacturer model: German NETZSCH DSC 3500Sirius
[0107] The finished products of Example 1, Example 2 and Example 3 were tested for various performance indicators according to corresponding experimental standards, and the test results are shown in the following table.
[0108]
[0109]
[0110] The results show that Examples 1, 2 and 3 of the present invention have the characteristics of high phase change enthalpy and high thermal conductivity, indicating that the present invention can effectively improve energy storage and release efficiency, improve thermal conductivity, dissipate heat in time, and increase the service life of the device.
[0111] (2) Cohesive strength test
[0112] The phase change coatings of Example 1, Example 2, and Example 3 were coated on a PET film, and the thickness of the phase change coating was 50 um. After coating, the upper and lower surfaces of the phase change coating were covered with a 20 um thick PET film, and the cohesive strength test was performed before and after 1000 hours of double 85 static (85°C temperature and 85% humidity).
[0113] The specific test method is: use the tensile testing machine fixture to clamp two layers of 20um PET film and perform a 180° peel force test.
[0114] The test data is as follows:
[0115]
[0116] The results show that the peeling force of the phase change coating of the present invention does not change before and after being left at 85°C (85% humidity), indicating that the adhesion strength between the coating and the release film has not changed, and further indicating that the cohesive strength of the coating has not changed. Therefore, the structure of the phase change coating of the present invention remains stable under high temperature and high humidity conditions, that is, when the operating temperature is continuously high, the phase change material of the present invention still maintains good cohesive strength, the components do not separate, the phase change coating does not dry out and harden, does not increase thermal resistance, and can effectively maintain high thermal conductivity efficiency.
Claims
1. A thermally conductive phase change coating, comprising a bonding material, a solvent, an initiator, a thermally conductive filler, a phase change material, and a wetting and dispersing agent, characterized in that: The following components are included in weight fractions: Isooctyl acrylate: 12%~14% Vinyl acetate: 4% to 6% Acrylic acid: 2% to 4% Expanded graphite: 2%~5% Phase change material: 50%~70% Initiator: 0.1%~0.5% Solvent: 8%~10% Wetting and dispersing agent: 1% to 5% 2. The thermally conductive phase change coating according to claim 1, characterized in that: The phase change material is paraffin, vaseline or a combination thereof.
3. The thermally conductive phase change coating according to claim 1, characterized in that: The initiator is benzoyl peroxide, and the ratio of the initiator to the adhesive is 0.2:14 to 0.2:
21.
4. The thermally conductive phase change coating according to claim 1, characterized in that: The solvent is toluene.
5. The thermally conductive phase change coating according to claim 1, characterized in that: The ratio of isooctyl acrylate:vinyl acetate:acrylic acid is 8.7:3.3:
2.
6. The thermally conductive phase change coating according to claim 2, characterized in that: The ratio of wetting and dispersing additive to expanded graphite ranges from 2:3 to 2:
8.
7. The thermally conductive phase change coating according to claim 1, characterized in that: The density of the expanded graphite is 1.5-2.1 g / cm3, and the crystal particle size is 0.15-0.3 mm.
8. The thermally conductive phase change coating according to claim 2, characterized in that: Phase change paraffin is a straight-chain alkane with 26 carbon atoms, accounting for 60% to 70% of the prescription.
9. The thermally conductive phase change coating according to claim 1, characterized in that: The wetting and dispersing agent is a polyamino cationic perylene imide graphene dispersant.
10. A method for preparing the thermally conductive phase change coating according to claim 1, 2, 3, 4, 5, 6, 7, 8 or 9, characterized in that: The following steps are involved: (1) Put isooctyl acrylate, isooctyl acetate, acrylic acid, and part of toluene into a 4-mouth reaction bottle, and set the external temperature to above 82°C; (2) When the temperature of the material in the bottle rises to 79°C, the BPO solution dissolved in the remaining toluene is evenly added dropwise into the reaction bottle within 2 hours; (3) Keep the reaction warm for 2 to 4 hours; (4) Add phase change paraffin and wetting dispersant into the reaction bottle and stir rapidly for 30 to 60 minutes; (5) Slowly add expanded graphite into the reaction bottle in batches; (6) After stirring and dispersing for 120 minutes, the mixture is applied while maintaining the temperature.
Citation Information
Patent Citations
Energy-storage phase-change film composite material, preparation method and application thereof
CN111959072A
EB curing copper-clad aluminum substrate heat dissipation coating
CN112961600A
Phase-change heat conduction slurry, heat conduction diaphragm and lithium ion battery
CN113652211A
Phase change composite material as well as preparation method and application thereof
CN119144158A
Producing heat-accumulating material containing binder, useful e.g. as adhesive, comprises emulsifying monomers and heat-accumulating material in water, initiating free radical polymerization and optionally drying the dispersion
DE102008043982A1
Cited By
Phase change energy storage coating based on micro-nano cavity structure and preparation method thereof
CN121696107A
Organosilicon phase change energy storage coating and preparation method thereof
CN122037784A
Heat-conducting phase-change material as well as preparation method and application thereof
CN122234762A